Vegetative propagation of labisia pumila roxb. By rooting of cuttings - Jane Diane, Anak Peter Ah-Came (Universiti Malaysia Sarawak, UNIMAS, 2012)
Labisia pumila (Kacip Fatimah) is one of important herb used widely among women. This study was conducted to determine the effect of watering system (non-mist and mist system), rooting medium (sand and coconut peat), application of rooting hormone (with rooting hormone and without rooting hormone) and leaf cuttings size (10 cm², 20 cm² and 40 cm²) on rooting of Labisia pumila var. pumila leaf cuttings. The leaf cuttings were assessed for rooting percentages of rooted cuttings, root length, number of root per rooted cutting and mortality percentages. Under mist system, the cuttings seemed to root better with 72.5% rooted cuttings compared to nonmist system with 56.25% of rooted cuttings. Cuttings planted on coconut peat achieved higher percentages of rooted cuttings compared to those planted on sand. Untreated cuttings appeared to root better than the cuttings treated with rooting hormone. Bigger leaf cuttings size had better result on rooting success than those smaller leaf cuttings size. Percentages of mortality showed that Labisia pumila var. pumila leaf cuttings planted on sand showed none of the cuttings die under non-mist and mist system while leaf cuttings planted on coconut peat showed 10.83% of dead leaf cuttings under non-mist system and 0.83% of dead leaf cuttings under mist system.